Chemistry IBSE Activities with Probeware: Pupil’s Motivational Orientation - Šmejkal, Petr; Skoršepa, Marek; Stratilová Urválková, Eva; Teplý, Pavel (Scientia in educatione, 2016)
The key factor in science education is motivation. Suitable motivation can simplify the educational process, it can involve pupils in studied phenomena, support the knowledge retention, etc. Basic knowledge related to motivation in case of some specific areas of education can help make education more effective and interesting. To employ motivational potential of suitably selected factors (i.e., connection with real life, employment of ICT, . . . ) in class effectively, it is valuable to know the motivation orientation of pupils as well as the factors which influence it. The article is focused on the study and evaluation of pupils’ motivational orientations when performing IBSE (Inquire based science education) activities with implemented MBL (probeware). An important motivation element is connecting the objectives of the activities to “real life” problems. For studying and evaluation of the motivational orientations, pupils filled in two questionnaires (pre- and post-) based on two validated tools: (i) Motivated Strategies for Learning Questionnaire (MSLQ) and (ii) Intrinsic Motivation Inventory (IMI). The questionnaires were statistically evaluated via the reliability test (Cronbach’s alpha), the analysis of variance (one-way ANOVA) and cluster analysis. The results showed that the majority of pupils were highly motivated before the course and their motivation increased after the laboratory course. The activities themselves were also evaluated positively, especially those focused on human body (effectivity of antacids) or medialized current affairs (gas chromatography — methanol affair). ANOVA testing showed that the key factor influencing motivational orientations are both the school attended and the chemistry teacher. On the contrary, motivational orientations are not very affected by gender or by the activity performed. Overall, pupils enjoyed the activities and work with MBL and they are in favour of implementing MBL into secondary school laboratories.